Sir Morien : the legend of a knight of the Round Table - Black, Holly; Smith, Kaliis (Little, Brown and Company, 2023)
Sir Morien sets off from Africa in search of his father, and meets Sir Gawain and Sir Lancelot who invite him to join their quest.